Efeitos da prática esportiva no comportamento pró-social dos indivíduos - SOUZA, Wagner Augusto Guedes (2022)
This study aims to analyze the behavior of the practitioner and the sports, which can be collective or individual. From the analysis of articles that relate sport as a transformative agent and the relation of the values added to its practice, we searched through a questionnaire. to establish a relationship between possible behavioral changes of those involved in sports practice. From the analysis of data collected during this research and understanding the importance of physical activity not only in the sports context, we prove through the responses of respondents the fundamental role of sport in the social behavior of individuals. We observed that the vast majority of individuals who participated in the research signaled positive changes in family relationships, disciplinary, respect and self-esteem. The next objective was of a comparative nature, in which we aim to present possible differences in the assimilation of these values added to the sports modalities by the athletes and how it is applied within the sports environment, the analysis of the results showed a very significant difference between the practitioners of the sports. that were the object of this study.